Teaching the theme periodic table in basic education (Research, Society and Development, 2020)
The teaching of the periodic table of basic education is present introductory in the 9th grade of elementary school and more deeply in the 1st year of high school. Regardless of the level of approach, its teaching still occurs traditionally in many educational institutions, based on exhaustive memorization of the organizational structure and properties of the elements. This teaching process makes the periodic table a low interest content and neglects the historical process of its construction. In this sense, this article aims to discuss and encourage the adoption of an approach involving the history of science in a contextualized way, in addition to the adoption of other didactic resources, not just the printed table. To this end, we present a brief bibliographical review about the history of the periodic table and its approach in the classroom. It is also suggested the use of different methodologies for teaching the theme in basic education.